(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The purpose of this work is to analyze the key competencies in the process of teaching foreign languages. Special attention is paid to linguistic and cultural competence, and it is emphasized that its formation is one of the mandatory conditions for comprehensive training of foreign students and improving the professionalism of future specialists. The results of this study can be applied for creating of the system of tasks and exercises in teaching foreign language, and foreign languages in higher educational establishments.